2013
DOI: 10.1002/2013ja019342
|View full text |Cite
|
Sign up to set email alerts
|

First results from CSSWE CubeSat: Characteristics of relativistic electrons in the near‐Earth environment during the October 2012 magnetic storms

Abstract: [1] Measurements from the Relativistic Electron and Proton Telescope integrated little experiment (REPTile) on board the Colorado Student Space Weather Experiment (CSSWE) CubeSat mission, which was launched into a highly inclined (65°) low Earth orbit, are analyzed along with measurements from the Relativistic Electron and Proton Telescope (REPT) and the Magnetic Electron Ion Spectrometer (MagEIS) instruments aboard the Van Allen Probes, which are in a low inclination (10°) geo-transfer-like orbit. Both REPT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 59 publications
2
67
0
1
Order By: Relevance
“…In this case, the lifetime computed is simply an upper limit on the true lifetime. Even more detail on the drift‐diffusion model itself can be examined in Selesnick [] and a previous application of the Loss Index Method is contained in Li et al [].…”
Section: Slow Decay and Loss Quantificationmentioning
confidence: 99%
“…In this case, the lifetime computed is simply an upper limit on the true lifetime. Even more detail on the drift‐diffusion model itself can be examined in Selesnick [] and a previous application of the Loss Index Method is contained in Li et al [].…”
Section: Slow Decay and Loss Quantificationmentioning
confidence: 99%
“…for space weather monitoring purposes (cf. Li et al, 2013). The CubeSat specification, however, constrains both dimensions (a three-unit CubeSat is 10 cm × 10 cm × 30 cm with 48 31 * The attitude mode data used in this paper were taken from housekeeping data; hence, they have a lower time resolution than specified in Brown et al (2014). no protuberant parts at launch) and total mass ( 4 kg for 3U) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although a net intensification, REPTile measurements during this storm separate the contribution of loss mechanisms from the net acceleration that occurred, specifically by quantifying the relative contribution from precipitation loss. Results from CSSWE analysis for the storm and succeeding electron flux increase are published in Li et al [10]. The authors showed that, when including atmospheric precipitation, the enhancement was at least 12.7% and 14.6% stronger for 0.58 MeV and 1.63 MeV electrons, respectively.…”
Section: Electrons In the Radiation Belts -Applicationsmentioning
confidence: 99%
“…When requested, the raw counts are transmitted to the ground where they are processed into differential flux units. Details of this conversion are specified in Li et al [10]. …”
Section: Instrument Designmentioning
confidence: 99%